The Effect of Different Media Content on Protease Activity Bacillus subtilis - Nurkasanah, Siti; Widodo, Nashi (Biotropika: Journal of Tropical Biology, 2015)
ABSTRACT Enzymes were protein molecules that synthesized cells to accelerate biochemical reactions. One of the microorganisms that produce a protease was Bacillus subtilis. B. subtilis used in this research consisted of isolate 1 and isolate 2. Methods used include thequalitative assay of protease activity through theclear zone on skim milk agar and calculation of protease activity on production media such as NB (Nutrient Broth) and TSB (Tryptic Soy Broth). Based on the results revealed that the clear zonediameter isolate 2 better than the isolate 1 after 24hours and 48 hours incubation periods. It showed both isolates having the possibility in different strains but within a species. The highest protease activity calculation obtained from TSB production media respectivelyÂ  0,14 Unit /ml unit and 0.12 Unit/ml. Keywords:B. subtilis, clear zone, protease, TSB